Associations between ultra-processed foods intake and preserved ratio impaired spirometry in U.S. adults - Kong, Weiliang (Frontiers in Nutrition, 2025)
BackgroundPreserved Ratio Impaired Spirometry (PRISm) is increasingly recognized as a precursor to Chronic Obstructive Pulmonary Disease (COPD). The impact of Ultra-Processed Foods (UPFs) intake on PRISm and lung function remains underexplored, and we aimed to explore their associations.MethodsThis study included 8,336 U.S. adults. Weighted logistic and linear regression models were employed for main analysis. Dose–response relationship was examined through restricted cubic spline (RCS) analysis, and subgroup analyses explored interactions with selected covariates.ResultsParticipants in the PRISm group were older and exhibited various adverse health characteristics. The percentage of total daily energy intake from UPFs (%Kcal) intake was associated with a non-significant increase in PRISm risk (OR 1.67, 95% CI: 0.96–2.92, p = 0.07). However, the highest quartile of UPFs (%Kcal) intake was significantly linked to increased PRISm risk (OR 1.36, 95% CI: 0.99–1.86, P for trend = 0.043). Furthermore, higher UPFs (%Kcal) intake negatively affected lung function, with participants in the highest quartile showing a significant reduction in forced expiratory volume in 1 s (FEV1) of −45.5 mL (95% CI: −87.6 to −3.4, P for trend = 0.045) and a decrease in forced vital capacity (FVC) of −139.4 mL (95% CI: −223.5 to −55.4, p < 0.001) compared to those in the lowest quartile. RCS analysis demonstrated linear relationships for both PRISm and lung function. Subgroup analysis revealed increased susceptibility primarily among individuals with occupational exposure. Additionally, sensitivity analysis indicated that a higher percentage of total daily intake from UPFs (%Grams) intake was significantly associated with an increased risk of PRISm (OR 1.86, 95% CI: 1.07–3.25, p = 0.03).ConclusionHigher intake of UPFs is linked to an increased risk of PRISm and negatively affects lung function, particularly in individuals with occupational exposure.